Kinanthropometric attributes of elite South African male kata and kumite karateka - Nichas, A.; Millard, L.; Shaw, B.; Breukelman, G.; Shaw, I. (Archives of Budo, 2020)
Background and Study Aim: Karate performance is based on many factors, such as strength, speed and endurance. Another important factor which can affect performance is kinanthropometric attributes. The cognitive aim of this study was to increase the knowledge about kinanthropometric attributes of South African male athletes participating in karate kata and kumite between the ages of 18-65 years.